Enhanced Cycling Stability of Cation Disordered Rock-Salt Li1.2Ti0.4Mn0.4O2 Material by Surface Modification With Al2O3 - Huang, Baojun; Wang, Rui; Gong, Yansheng; He, Beibei; Wang, Huanwen (Frontiers in Chemistry, 2019)
Cation disordered rock-salt lithium-excess oxides are promising candidate cathode materials for next-generation electric vehicles due to their extra high capacities. However, one major issue for these materials is the distinct decline of discharge capacities during charge/discharge cycles. In this study, Al2O3 layers were coated on disordered Li1.2Ti0.4Mn0.4O2 (LTMO) using atomic layer deposition (ALD) method to optimize its electrochemical performance. The discharge capacity after 15 cycles increased from 228.1 mAh g-1 to 266.7 mAh g-1 for LTMO after coated with Al2O3 for 24 ALD cycles, and the corresponding capacity retention enhanced from 79.7% to 90.9%. The improved cycling stability of the coated sample was ascribed to the alleviation of oxygen release and the inhibition on the undesirable side reactions. Our work has provided a new possible solution to address some of the capacity fading issues related to the disordered rock-salt cathode materials.